Efficacy of double-buffered sodium butyrate supplementation in low energy-protein broiler diets - Iglesias, Bernardo Fabricio; Charriere, Maria Viviana; Fain Binda, Virginia; Marecaille, C.; Melo, J. (World’s Poultry Science Association, 2025)
Poster y resumen